A highly stable salt spray resistant aqueous acrylic emulsion and preparation method thereof
By using dendritic polymer monomers in aqueous acrylic emulsions with carbon nanotubes and nanotitanium dioxide shells, the problem of insufficient gloss and salt spray resistance of the existing aqueous acrylic emulsions is solved, high stability, salt spray resistance and thermal stability are achieved, and the gloss and salt spray resistance of the coating are improved.
Patent Information
- Application Number
- CN202510037674.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The gloss and salt spray resistance of existing aqueous acrylic emulsions are generally not high, and cannot meet the requirements of high-end products, and their dispersion stability and thermal stability are insufficient.
A high stability and salt spray-resistant aqueous acrylic emulsion is used to prepare a high-stable, salt-smoke-resistant aqueous acrylic emulsion, and the dendrimer is formed by reacting end amino polyamide with acrylic chloride, and is compounded with butyl acrylate, styrene, etc., and combined with carbon nanotubes and nanotitanium dioxide shells to form a high crosslinking and stability system.
It achieves high stability, salt spray resistance and thermal stability, high coating gloss, salt spray resistance time exceeds 1000 hours, and has high gloss and ultra-long salt spray resistance.
Smart Images

Figure CN119432225B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of acrylic emulsions, and in particular to a highly stable salt spray resistant aqueous acrylic emulsion and a preparation method thereof. Background Art
[0002] At present, water-based acrylic emulsion has excellent weather resistance, mechanical properties, acid and alkali resistance, etc., which gives it a wide range of application advantages. It is crucial to reduce VOC emissions and make the entire emulsion industry develop in an environmentally friendly, green and sustainable manner.
[0003] Water-based acrylic emulsion is usually prepared by emulsion polymerization. It uses water-based acrylic resin formed by polymerization of acrylic monomers or acrylate monomers as the film-forming material. It exhibits excellent performance in corrosion resistance, water resistance, and alkali resistance, and has good color retention and excellent film formation. It has now been widely used.
[0004] However, the gloss and salt spray resistance of existing water-based acrylic emulsions are generally not high, which cannot meet the requirements of high-end products, and the performance of a single acrylic emulsion is difficult to meet the requirements of coating. The gloss of acrylic emulsions prepared by nano-titanium dioxide doping is currently greatly improved, but the dispersion stability of water-based emulsions is poor, and the salt spray resistance and thermal stability cannot be guaranteed, which needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a highly stable salt spray resistant aqueous acrylic emulsion and a preparation method thereof.
[0006] A method for preparing a highly stable salt spray resistant water-based acrylic emulsion comprises the following steps:
[0007] S1. Add amino-terminated polyamidoamine to dichloromethane and stir evenly, add acryloyl chloride dropwise thereto under stirring, stir at 20-40° C. for 5-10 hours, filter, remove dichloromethane by rotary evaporation, add to water, then add butyl acrylate, styrene, 3-mercaptopropionic acid, acrylic acid, and emulsifier thereto, stir at 30-40° C. for 10-20 minutes to obtain preform a;
[0008] S2, adding sodium carbonate to water and stirring for 10-20 seconds, then adding preform a, stirring evenly at 70-80°C, adding sodium persulfate and continuing stirring for 10-20 minutes to obtain preform b;
[0009] S3, adding carbon nanotubes to ethanol aqueous solution and ultrasonically dispersing them uniformly, adjusting the pH value of the system to 9-10, adding tetrabutyl titanate thereto, ultrasonically treating at 40-60° C. for 5-10 min, adding triethylamine and silane coupling agent and continuing ultrasonically treating for 1-2 h, centrifuging, washing, and vacuum drying to obtain preform c;
[0010] S4. Add prefabricated material a to prefabricated material b, stir at 80-87℃ for 3-5h, reduce to 40-50℃, add ammonium persulfate and stir for 10-30min, filter, add prefabricated material c, dispersant, anti-rust pigment and water, mix evenly, grind to a fineness of less than 10µm, and filter.
[0011] Preferably, in S1, the generation number of the amino-terminated polyamidoamine is 1.5-3.5 generations.
[0012] Preferably, the mass ratio of amino-terminated polyamidoamine, acryloyl chloride, butyl acrylate, styrene, 3-mercaptopropionic acid, acrylic acid, emulsifier and water is 5-10:1-3:20-40:15-30:1-2:1-3:1-2:20-50.
[0013] Preferably, in S1, the emulsifier is Tween and / or Span.
[0014] Preferably, in S2, the mass ratio of sodium carbonate, preform a and sodium persulfate is 0.1-1:3.2-14:0.1-1.
[0015] Preferably, in S3, the mass ratio of carbon nanotubes, tetrabutyl titanate, triethylamine and silane coupling agent is 1-2:5-10:0.1-1:1-2.
[0016] Preferably, in S3, the silane coupling agent is γ-aminopropyltriethoxysilane.
[0017] Preferably, in S3, the ultrasonic frequency is 5-15 kHz.
[0018] Preferably, in S4, the mass ratio of preform a, preform b, preform c, ammonium persulfate, dispersant, anti-rust pigment and water is 60.8-126:5-15:7-15:1-2:1-2:1-2:10-20.
[0019] Preferably, in S4, after grinding, filtering is performed using a 200-mesh filter.
[0020] A highly stable salt spray resistant water-based acrylic emulsion is prepared by adopting the preparation method of the highly stable salt spray resistant water-based acrylic emulsion. Beneficial Effects
[0021] The invention is green and environmentally friendly, can not only disperse to form a stable emulsion, but also has excellent film-forming density, improved water resistance and salt spray resistance, and greatly enhanced heat resistance and stability.
[0022] The present invention utilizes terminal amino polyamidoamine with a dendritic macromolecular structure to react with acryloyl chloride to form a polymerized monomer, which not only has good fluidity, but also is compounded with butyl acrylate, styrene, 3-mercaptopropionic acid and acrylic acid to effectively improve the glossiness of the emulsion after curing. At the same time, the dendritic structure voids can effectively accommodate the prefabricated material C, and after curing, it has a higher cross-linking degree, effectively improves adhesion and hardness, and also improves thermal stability and salt spray resistance.
[0023] The present invention coats a nano titanium dioxide shell layer on the surface of the carbon nanotube, which not only has excellent thermal stability, but also can be evenly dispersed in the matrix and easily accommodated in the gaps of the dendritic structure after surface amination. The system stability is stronger, and the molecular chain is not easy to curl and fold even under high temperature conditions, thereby ensuring the viscosity of the system in a high temperature environment, and having better salt spray resistance stability after curing.
[0024] The test results show that the aqueous emulsion obtained by the present invention has strong stability, suitable emulsion viscosity, is not easy to sag, has beautiful appearance after film formation, is resistant to salt spray, and has excellent heat resistance stability. After curing, the salt spray resistance time is greater than 1000h, and the gloss value can reach above 90.5, with both high gloss and ultra-long salt spray resistance. It also has a certain washability and excellent comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a comparison chart of the viscosities of the aqueous acrylic emulsions obtained in Example 5 and Comparative Examples 1-2 at room temperature and 40°C.
[0026] Figure 2 This is a comparison chart of the 60° gloss values of coatings made from the water-based acrylic emulsions obtained in Example 5 and Comparative Examples 1-2.
[0027] Figure 3 Thermogravimetric analysis curves of coatings made from the aqueous acrylic emulsions obtained in Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0028] The present invention will be further explained below in conjunction with specific embodiments.
[0029] Example 1 A method for preparing a highly stable salt spray resistant aqueous acrylic emulsion comprises the following steps:
[0030] S1. Add 5 g of 1.5-generation amino-terminated polyamidoamine to 30 g of dichloromethane and stir evenly. Add 1 g of acryloyl chloride dropwise thereto under stirring, stir at 20° C. for 5 h, filter, remove dichloromethane by rotary evaporation, add 20 g of deionized water, add 20 g of butyl acrylate, 15 g of styrene, 1 g of 3-mercaptopropionic acid, 1 g of acrylic acid, and 1 g of Span 60, stir at 30° C. for 10 min at a stirring speed of 100 r / min, and obtain preform a;
[0031] S2, add 0.1g sodium carbonate to 1g deionized water and stir for 10s, then add 3.2g preform a, stir evenly at 70°C, add 0.1g sodium persulfate and continue stirring for 10min to obtain preform b;
[0032] S3, adding 1g of carbon nanotubes to 20g of 40% ethanol aqueous solution by ultrasonic dispersion, the ultrasonic frequency is 5kHz, the pH value of the system is adjusted to 9-10 with ammonia water, 5g of tetrabutyl titanate is added thereto, ultrasonic treatment is carried out at a temperature of 40°C for 5min, the ultrasonic frequency is 5kHz, 0.1g of triethylamine and 1g of γ-aminopropyltriethoxysilane are added, and ultrasonic treatment is continued for 1h, centrifugation, washing, and vacuum drying to obtain preform c;
[0033] S4. Add 60.8g of preform a to 5g of preform b, stir at 80°C for 3h, cool to 40°C, add 1g of ammonium persulfate, stir for 10min, filter, add 7g of preform c, 1g of dispersant, 1g of anti-rust pigment, and 10g of deionized water, mix well, send to a sand mill, grind to a fineness of less than 10µm, and pass through a 200-mesh filter.
[0034] Example 2 A method for preparing a highly stable salt spray resistant aqueous acrylic emulsion comprises the following steps:
[0035] S1. Add 10 g of 3.5-generation amino-terminated polyamidoamine to 60 g of dichloromethane and stir evenly. Add 3 g of acryloyl chloride dropwise thereto under stirring. Stir at 40 ° C for 10 h. Filter. Remove dichloromethane by rotary evaporation. Add 50 g of deionized water. Add 40 g of butyl acrylate, 30 g of styrene, 2 g of 3-mercaptopropionic acid, 3 g of acrylic acid and 2 g of Tween 60. Stir at 40 ° C for 20 min at a stirring speed of 500 r / min to obtain preform a.
[0036] S2, add 1g of sodium carbonate to 3g of deionized water and stir for 20s, then add 14g of preform a, stir evenly at a temperature of 80°C, add 1g of sodium persulfate and continue stirring for 20min to obtain preform b;
[0037] S3, adding 1-2g carbon nanotubes to 50g 60% ethanol aqueous solution and uniformly dispersing by ultrasonication, the ultrasonic frequency is 15kHz, using ammonia water to adjust the pH value of the system to 9-10, adding 10g tetrabutyl titanate thereto, ultrasonically treating at 60°C for 10min, the ultrasonic frequency is 15kHz, adding 1g triethylamine and 2g γ-aminopropyltriethoxysilane and continuing ultrasonication for 2h, centrifuging, washing, and vacuum drying to obtain preform c;
[0038] S4. Add 126g of preform a to 15g of preform b, stir at 87°C for 5h, cool to 50°C, add 2g of ammonium persulfate, stir for 30min, filter, add 15g of preform c, 2g of dispersant, 2g of anti-rust pigment, and 20g of deionized water, mix well, send to a sand mill, grind to a fineness of less than 10µm, and pass through a 200-mesh filter.
[0039] Example 3 A method for preparing a highly stable salt spray resistant aqueous acrylic emulsion comprises the following steps:
[0040] S1. Add 7 g of 3.0-generation amino-terminated polyamidoamine to 40 g of dichloromethane and stir evenly. Add 2.5 g of acryloyl chloride dropwise thereto under stirring, stir at 25 ° C for 9 h, filter, remove dichloromethane by rotary evaporation, add 30 g of deionized water, add 35 g of butyl acrylate, 20 g of styrene, 1.8 g of 3-mercaptopropionic acid, 1.5 g of acrylic acid, and 1.7 g of Span 80, stir at 33 ° C for 18 min, and stir at a speed of 200 r / min to obtain preform a;
[0041] S2, adding 0.7 g of sodium carbonate to 1.5 g of deionized water and stirring for 15 seconds, then adding 12 g of preform a, stirring evenly at a temperature of 73° C., adding 0.7 g of sodium persulfate and continuing stirring for 12 minutes to obtain preform b;
[0042] S3, adding 1.7g of carbon nanotubes to 30g of 55% ethanol aqueous solution and uniformly dispersing by ultrasonication, the ultrasonic frequency is 9kHz, and the pH value of the system is adjusted to 9-10 by using ammonia water, adding 9g of tetrabutyl titanate thereto, ultrasonically treating at a temperature of 45°C for 9min, the ultrasonic frequency is 9kHz, adding 0.7g of triethylamine and 1.2g of γ-aminopropyltriethoxysilane and continuing ultrasonication for 100min, centrifuging, washing, and vacuum drying to obtain preform c;
[0043] S4. Add 120g of preform a to 8g of preform b, stir at 82°C for 4.5h, cool to 42°C, add 1.7g of ammonium persulfate, stir for 15min, filter, add 13g of preform c, 1.3g of dispersant, 1.8g of anti-rust pigment, and 12g of deionized water, mix well, send to a sand mill, grind to a fineness of less than 10µm, and pass through a 200-mesh filter.
[0044] Example 4 A method for preparing a highly stable salt spray resistant aqueous acrylic emulsion comprises the following steps:
[0045] S1. Add 9 g of 2.5-generation amino-terminated polyamidoamine to 50 g of dichloromethane and stir evenly. Add 1.5 g of acryloyl chloride dropwise thereto under stirring. Stir at 35 ° C for 7 h. Filter. Remove dichloromethane by rotary evaporation. Add 40 g of deionized water. Add 25 g of butyl acrylate, 28 g of styrene, 1.2 g of 3-mercaptopropionic acid, 2.5 g of acrylic acid and 1.3 g of Tween 80. Stir at 37 ° C for 12 min at a stirring speed of 400 r / min to obtain preform a.
[0046] S2, adding 0.3 g of sodium carbonate to 2.5 g of deionized water and stirring for 15 seconds, then adding 6 g of preform a, stirring evenly at a temperature of 77° C., adding 0.3 g of sodium persulfate and continuing stirring for 18 minutes to obtain preform b;
[0047] S3, adding 1.3g of carbon nanotubes to 40g of 45% ethanol aqueous solution by ultrasonic dispersion, the ultrasonic frequency is 12kHz, the pH value of the system is adjusted to 9-10 with ammonia water, adding 7g of tetrabutyl titanate thereto, ultrasonic treatment at a temperature of 55°C for 7min, the ultrasonic frequency is 12kHz, adding 0.3g of triethylamine and 1.8g of γ-aminopropyltriethoxysilane, and continuing ultrasonic treatment for 80min, centrifuging, washing, and vacuum drying to obtain preform c;
[0048] S4. Add 66g of preform a to 12g of preform b, stir at 86°C for 3.5h, cool to 48°C, add 1.3g of ammonium persulfate, stir for 25min, filter, add 10g of preform c, 1.7g of dispersant, 1.2g of anti-rust pigment, and 18g of deionized water, mix well, send to a sand mill, grind to a fineness of less than 10µm, and pass through a 200-mesh filter.
[0049] Example 5 A method for preparing a highly stable salt spray resistant aqueous acrylic emulsion comprises the following steps:
[0050] S1. Add 8 g of 2.0 generation amino-terminated polyamidoamine to 45 g of dichloromethane and stir evenly. Add 2 g of acryloyl chloride dropwise thereto under stirring. Stir at 30 ° C for 8 h. Filter. Remove dichloromethane by rotary evaporation. Add 35 g of deionized water. Add 30 g of butyl acrylate, 24 g of styrene, 1.5 g of 3-mercaptopropionic acid, 2 g of acrylic acid and 1.5 g of Tween 80. Stir at 35 ° C for 15 min at a stirring speed of 300 r / min to obtain preform a.
[0051] S2, adding 0.5g of sodium carbonate to 2g of deionized water and stirring for 15s, then adding 9g of preform a, stirring evenly at a temperature of 75°C, adding 0.5g of sodium persulfate and continuing stirring for 15min to obtain preform b;
[0052] S3, adding 1.5g of carbon nanotubes to 35g of 50% ethanol aqueous solution by ultrasonic dispersion, the ultrasonic frequency is 10.5kHz, the pH value of the system is adjusted to 9-10 with ammonia water, adding 8g of tetrabutyl titanate thereto, ultrasonic treatment at a temperature of 50°C for 8min, the ultrasonic frequency is 10.5kHz, adding 0.5g of triethylamine and 1.5g of γ-aminopropyltriethoxysilane, and continuing ultrasonic treatment for 90min, centrifuging, washing, and vacuum drying to obtain preform c;
[0053] S4. Add 93g of preform a to 10g of preform b, stir at 84°C for 4h, cool to 45°C, add 1.5g of ammonium persulfate, stir for 20min, filter, add 12g of preform c, 1.5g of dispersant, 1.5g of anti-rust pigment, and 15g of deionized water, mix well, send to a sand mill, grind to a fineness of less than 10µm, and pass through a 200-mesh filter.
[0054] Comparative Example 1 A method for preparing an aqueous acrylic emulsion comprises the following steps:
[0055] S1, adding 8 g of 2.0 generation amino-terminated polyamidoamine to 35 g of deionized water, adding 30 g of butyl acrylate, 24 g of styrene, 1.5 g of 3-mercaptopropionic acid, 2 g of acrylic acid, and 1.5 g of Tween 80 thereto, stirring at a temperature of 35° C. for 15 min at a stirring speed of 300 r / min to obtain preform a;
[0056] S2, adding 0.5g of sodium carbonate to 2g of deionized water and stirring for 15s, then adding 9g of preform a, stirring evenly at a temperature of 75°C, adding 0.5g of sodium persulfate and continuing stirring for 15min to obtain preform b;
[0057] S3, adding 1.5g of carbon nanotubes to 35g of 50% ethanol aqueous solution by ultrasonic dispersion, the ultrasonic frequency is 10.5kHz, the pH value of the system is adjusted to 9-10 with ammonia water, adding 8g of tetrabutyl titanate thereto, ultrasonic treatment at a temperature of 50°C for 8min, the ultrasonic frequency is 10.5kHz, adding 0.5g of triethylamine and 1.5g of γ-aminopropyltriethoxysilane, and continuing ultrasonic treatment for 90min, centrifuging, washing, and vacuum drying to obtain preform c;
[0058] S4. Add 93g of preform a to 10g of preform b, stir at 84°C for 4h, cool to 45°C, add 1.5g of ammonium persulfate, stir for 20min, filter, add 12g of preform c, 1.5g of dispersant, 1.5g of anti-rust pigment, and 15g of deionized water, mix well, send to a sand mill, grind to a fineness of less than 10µm, and pass through a 200-mesh filter.
[0059] Comparative Example 2 A method for preparing an aqueous acrylic emulsion comprises the following steps:
[0060] S1. Add 8 g of 2.0 generation amino-terminated polyamidoamine to 45 g of dichloromethane and stir evenly. Add 2 g of acryloyl chloride dropwise thereto under stirring. Stir at 30 ° C for 8 h. Filter. Remove dichloromethane by rotary evaporation. Add 35 g of deionized water. Add 30 g of butyl acrylate, 24 g of styrene, 1.5 g of 3-mercaptopropionic acid, 2 g of acrylic acid and 1.5 g of Tween 80. Stir at 35 ° C for 15 min at a stirring speed of 300 r / min to obtain preform a.
[0061] S2, adding 0.5g of sodium carbonate to 2g of deionized water and stirring for 15s, then adding 9g of preform a, stirring evenly at a temperature of 75°C, adding 0.5g of sodium persulfate and continuing stirring for 15min to obtain preform b;
[0062] S3, weigh 35g of 50% ethanol aqueous solution, adjust the pH value of the system to 9-10 with ammonia water, add 8g of tetrabutyl titanate thereto, perform ultrasonic treatment at 50°C for 8min, the ultrasonic frequency is 10.5kHz, add 0.5g of triethylamine and 1.5g of γ-aminopropyltriethoxysilane, continue ultrasonic treatment for 90min, centrifuge, wash, and vacuum dry to obtain preform c;
[0063] S4. Add 93g of preform a to 10g of preform b, stir at 84°C for 4h, cool to 45°C, add 1.5g of ammonium persulfate, stir for 20min, filter, add 10.5g of preform c, 1.5g of carbon nanotubes, 1.5g of dispersant, 1.5g of anti-rust pigment, and 15g of deionized water, mix well, send to a sand mill, grind to a fineness of less than 10µm, and pass through a 200-mesh filter.
[0064] The viscosity of the aqueous acrylic emulsions obtained in Example 5 and Comparative Examples 1-2 at room temperature (25°C) and 40°C was measured. Figure 1 As shown, the viscosity of the three is similar at room temperature (P>0.05), all in the range of 330-345 mPa·s, but the viscosity of the aqueous acrylic emulsion obtained in Example 5 at 40°C is the lowest, which is better than that of Comparative Examples 1-2 (P<0.05), indicating that the viscosity of the aqueous acrylic emulsion obtained in the present invention is appropriate, stable between 300-500 mPa·s, and not easy to sag.
[0065] The aqueous acrylic emulsions obtained in Example 5 and Comparative Examples 1-2 were stored at room temperature for 9 months without any stratification or precipitation; and the freeze-thaw cycles of the three were all greater than 5.
[0066] The aqueous acrylic emulsions obtained in Example 5 and Comparative Examples 1-2 were coated on the surface of a transparent glass plate and baked in an oven at 80±1°C for 20 minutes. The thickness of each coating was 70±2 μm. The 60° gloss value of each coating was measured with reference to GB / T 9754-2007 "Determination of 20°, 60° and 85° specular gloss of paints and varnishes without metallic pigments".
[0067] like Figure 2 As shown, the gloss value of the water-based acrylic emulsion obtained in Example 5 is the highest, which is better than that of Comparative Examples 1-2 (P < 0.05).
[0068] The aqueous acrylic emulsions obtained in Example 5 and Comparative Examples 1-2 were coated on the surface of CR4 grade cold-rolled carbon steel plates and baked in an oven at 80±1°C for 20 minutes. The coating thickness of each group was 70±2μm. The coating hardness and salt spray corrosion resistance time of each group of coating samples were measured by referring to GB / T 6739-2022 "Determination of film hardness by pencil method for paints and varnishes" and GB / T 10125-2012 "Artificial atmosphere corrosion test salt spray test" NSS test, and the results are shown in Table 1.
[0069] Among them, the longest NSS test cycle is 1000h. When the mass of the sample changes, the test is stopped, and the time when the mass of the previous sample does not change is used as the salt spray corrosion resistance time.
[0070] Table 1 Coating hardness and salt spray corrosion resistance time of each group of coating samples
[0071] Example 5 Comparative Example 1 Comparative Example 2 Coating hardness 2H B HB Salt spray corrosion resistance time 1000h 504h 720h
[0072] It can be seen from Table 1 that the coating made from the water-based acrylic emulsion obtained in Example 5 has the highest hardness and the longest salt spray corrosion resistance time, which is better than Comparative Examples 1-2.
[0073] The aqueous acrylic emulsions obtained in Example 5 and Comparative Examples 1-2 were used for coating and then baked to form coatings. Samples were scraped for thermogravimetric analysis. The protective atmosphere was nitrogen, the pressure was 0.1 MPa, the flow rate was 100 mL / min, and the heating rate was 10° C. / min.
[0074] like Figure 3 As shown, the thermal stability of the coating obtained by coating the water-based acrylic emulsion obtained in Example 5 and then baking is the best, which is better than that of Comparative Examples 1-2.
[0075] The applicant believes that the reason for the above differences is that: the present invention utilizes the amino-terminated polyamide amine with a dendritic macromolecular structure to react with acryloyl chloride to form a polymerized monomer, which not only has good fluidity, but also is compounded with butyl acrylate, styrene, 3-mercaptopropionic acid, and acrylic acid, effectively improving the glossiness of the emulsion after curing. At the same time, the dendritic structure voids can effectively accommodate the preform c, and after curing, it has a higher degree of crosslinking, effectively improves adhesion and hardness, and improves thermal stability and salt spray resistance. At the same time, the present invention coats a layer of nano titanium dioxide shell on the surface of the carbon nanotube, which not only has excellent thermal stability, but also can be evenly dispersed in the matrix after surface amination, and is easily accommodated by the dendritic structure voids, and the system stability is stronger. Even under high temperature conditions, the molecular chain is not easy to curl and fold, ensuring the viscosity of the system in a high temperature environment, and the salt spray resistance stability is better after curing.
[0076] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a highly stable salt spray resistant aqueous acrylic emulsion, characterized in that: The steps include: S1. Add amino-terminated polyamidoamine to dichloromethane and stir evenly, add acryloyl chloride dropwise thereto under stirring, stir at 20-40° C. for 5-10 hours, filter, remove dichloromethane by rotary evaporation, add to water, then add butyl acrylate, styrene, 3-mercaptopropionic acid, acrylic acid, and emulsifier thereto, stir at 30-40° C. for 10-20 minutes to obtain preform a; The mass ratio of amino-terminated polyamidoamine, acryloyl chloride, butyl acrylate, styrene, 3-mercaptopropionic acid, acrylic acid, emulsifier and water is 5-10: 1-3: 20-40: 15-30: 1-2: 1-3: 1-2: 20-50; S2, adding sodium carbonate to water and stirring for 10-20 seconds, then adding preform a, stirring evenly at 70-80°C, adding sodium persulfate and continuing stirring for 10-20 minutes to obtain preform b; S3, adding carbon nanotubes to ethanol aqueous solution and ultrasonically dispersing them uniformly, adjusting the pH value of the system to 9-10, adding tetrabutyl titanate thereto, ultrasonically treating at 40-60° C. for 5-10 min, adding triethylamine and silane coupling agent and continuing ultrasonically treating for 1-2 h, centrifuging, washing, and vacuum drying to obtain preform c; S4, add preform a to preform b, stir at 80-87℃ for 3-5h, cool to 40-50℃, add ammonium persulfate and stir for 10-30min, filter, add preform c, dispersant, anti-rust pigment and water, mix evenly, grind to a fineness of less than 10µm, and filter; In S4, the mass ratio of preform a, preform b, preform c, ammonium persulfate, dispersant, anti-rust pigment and water is 60.8-126:5-15:7-15:1-2:1-2:1-2:10-20.
2. The method for preparing the highly stable salt spray resistant aqueous acrylic emulsion according to claim 1, characterized in that: In S1, the generation number of the amino-terminated polyamidoamine is 1.5-3.5 generations.
3. The method for preparing the highly stable salt spray resistant aqueous acrylic emulsion according to claim 1, characterized in that: In S1, the emulsifier is Tween and / or Span.
4. The method for preparing the highly stable salt spray resistant aqueous acrylic emulsion according to claim 1, characterized in that: In S2, the mass ratio of sodium carbonate, preform a and sodium persulfate is 0.1-1:3.2-14:0.1-1.
5. The method for preparing the highly stable salt spray resistant aqueous acrylic emulsion according to claim 1, characterized in that: In S3, the mass ratio of carbon nanotubes, tetrabutyl titanate, triethylamine and silane coupling agent is 1-2:5-10:0.1-1:1-2.
6. The method for preparing the highly stable salt spray resistant aqueous acrylic emulsion according to claim 1, characterized in that: In S3, the silane coupling agent is γ-aminopropyltriethoxysilane.
7. The method for preparing the highly stable salt spray resistant aqueous acrylic emulsion according to claim 1, characterized in that: In S3, the ultrasound frequency is 5-15kHz.
8. The method for preparing the highly stable salt spray resistant aqueous acrylic emulsion according to claim 1, characterized in that: In S4, after grinding, the product is filtered using a 200-mesh filter.
9. A highly stable salt spray resistant aqueous acrylic emulsion, characterized in that: The high-stability salt-spray-resistant aqueous acrylic emulsion is prepared by the preparation method of any one of claims 1 to 8.
Citation Information
Patent Citations
Anti-shearing polymer and preparation method thereof
CN102633955A
Unsaturated group-terminated aromatic polyamide oligomer and its production
JP1991050217A